2003
DOI: 10.1128/ec.2.6.1266-1273.2003
|View full text |Cite
|
Sign up to set email alerts
|

EAP1 , a Candida albicans Gene Involved in Binding Human Epithelial Cells

Abstract: Candida albicans adhesion to host tissues contributes to its virulence and adhesion to medical devices permits biofilm formation, but we know relatively little about the molecular mechanisms governing C. albicans adhesion to materials or mammalian cells. Saccharomyces cerevisiae provides an attractive model system for studying adhesion in yeast because of its well-characterized genetics and gene expression systems and the conservation of signal transduction pathways among the yeasts. In this study, we used a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 66 publications
7
154
0
Order By: Relevance
“…1B, D). The 42 aa repeat was shared by other C. albicans cell wall GPI-modified proteins, including the Cht2 chitinase (Dunkler et al, 2005;McCreath et al, 1995), Hwp1 (Staab & Sundstrom, 1998;Sundstrom, 2002), Hwp2 (Sohn et al, 2003), Rbt1 (Braun et al, 2000), Eap1 (Li & Palecek, 2003, Ywp1 (Granger et al, 2005;Sohn et al, 2003), and three putative GPI-modified proteins, Pga6, Pga18 and Pga38. In these proteins the amino acid repeat was 42-46 aa long (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1B, D). The 42 aa repeat was shared by other C. albicans cell wall GPI-modified proteins, including the Cht2 chitinase (Dunkler et al, 2005;McCreath et al, 1995), Hwp1 (Staab & Sundstrom, 1998;Sundstrom, 2002), Hwp2 (Sohn et al, 2003), Rbt1 (Braun et al, 2000), Eap1 (Li & Palecek, 2003, Ywp1 (Granger et al, 2005;Sohn et al, 2003), and three putative GPI-modified proteins, Pga6, Pga18 and Pga38. In these proteins the amino acid repeat was 42-46 aa long (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The C. albicans Eap1p adhesin was originally identified because of its ability to mediate adhesion to polystyrene when the EAP1 gene was expressed in a flocculin-deficient Saccharomyces cerevisiae strain. EAP1 expression enhanced attachment of S. cerevisiae to HEK293 kidney epithelial cells and played an additional role in mediating interactions between S. cerevisiae and C. albicans cells (Li & Palecek, 2003, 2005. Expression of EAP1 in a C. albicans efg1/efg1 mutant was able to restore its partially reduced adhesion to HEK293 epithelial cells (Li & Palecek, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…However, it has some benefits, as it provides quick and efficient method to screen multiple personal care ingredients singly and in combination. Polystyrene has long been used to measure how well bacteria and fungi attach to surfaces [12][13][14][15]. Previous studies have shown that studies on bacteria and fungi with mutations in attachment have also been shown respond to polystyrene and skin surfaces in similar ways [12,15].…”
Section: Discussionmentioning
confidence: 99%